Screening of m6A-associated ferroptosis-related genes in atherosclerosis based on WGCNA - Jiang, Meiling; Zhao, Weidong; Wu, Liyong; Zhu, Guofu (Frontiers in Cardiovascular Medicine, 2024)
Background: N6-methyladenosine (m6A) have been shown to mediate ferroptosis, but the role in atherosclerosis (AS)is unclear. Methods: Differentially expressed m6A-associated ferroptosis-related genes (DE-m6A-Ferr-RGs) were obtained by differential expression analysis and Pearson correlation analysis. Weighted gene co-expression network analysis (WGCNA) was also performed. The intersection of the module genes and the DE-m6A-Ferr-RGs were recorded as candidate m6A-Ferr-related signature genes. Finally, the m6A-Ferr-related signature genes were screened by lasso analysis. Expression validation, ROC mapping, and immune correlation analysis were also performed based on the m6A-Ferr-related signature genes. The expression of m6A-Ferr-related signature genes was further validated by RT-qPCR. Results: 6167 DEGs were intersected with 24 m6A-and 259 ferroptosis-related genes, respectively, resulting in 113 DE-m6A-Ferr-RGs by pearson correlation analysis. The module genes obtained from WGCNA analysis and the 113 DE-m6A-Ferr-RGs were intersected to obtain 48 candidate m6A-Ferr-related signature genes. Lasso analysis was performed and 6 m6A-Ferr-related signature genes were screened. In addition, the AUC values of all 6 m6A-Ferr-related signature genes were greater than 0.7, indicating that they had potential diagnostic values. Meanwhile, The RT-qPCR results revealed that the expression of SLC3A2, NOX4 and CDO1 was consistent with the transcriptome level. Moreover, 2 types of immune cells showed significant differences between AS and control groups. And naive B cells, CD8+ T cells, Tregs, and activated NK cells were positively correlated with CDO1 and NOX4, but negatively correlated with ATG7, CYBB, and SLC3A2. Conclusion: 3 m6A-Ferr-related signature genes (NOX4, CDO1, and SLC3A2) were obtained by a series of bioinformatics analyses and RT-qPCR.